Effect of garlic on serum cholesterol level in rats on high fat diets. - Sahabuddin, Mohd Shaun Farleen; Abdul Razak, Intan Shameha; Mohd Noor, Mohd Hezmee (2011)
Garlic has been reported to possess the effect of lowering serum cholesterol level in blood thus may reduced the occurrence of cardiovascular disease but scientific reports are lacking. Twenty-four Sprague-Dawley rats of 16-weeks old were divided into four groups (n = 6). Hypercholesterolemia was induced by feeding 20% butter as high fat diet for two weeks and the treatment diet for three weeks. Group A was fed normal diet, group B fed normal diet + butter, group C fed normal diet + butter + garlic and group D was fed normal diet + butter + dexamethasone. The serum cholesterol concentration, average body weight and organ weight were determined for five weeks. The results showed a significant (p<0.05) decrease in the serum total cholesterol concentration for groups C and D. The average body weight was significantly (p<0.05) different between the initial body weight and final body weight. The organ weight showed a significant (p<0.05) decrease in mean blotted dry liver weight in groups C and D. These observations indicate that consumption of raw garlic has beneficial effect in lowering serum total cholesterol concentration and promote weight control.